Infância, gênero e raça: perspectivas sociais na construção da identidade - Vicente, Isabella (Universidade Federal de São Carlos, 2025)
This undergraduate thesis investigates how children understand the concepts of gender and race during early childhood through a bibliographic review of dissertations and theses available in the Brazilian Digital Library of Theses and Dissertations (BDTD). Based on Vygotsky’s (1991) Socio-Historical Psychology, the study emphasizes the crucial role of social interactions—mediated by language and cultural contexts—in child development. The findings indicate a predominance of studies that address gender and race from adult perspectives, with little emphasis on the viewpoints of children themselves. It was also observed that most studies focus solely on gender issues, with few integrating both gender and race in a comprehensive manner. Furthermore, the research highlights the influence of schools and families in reproducing social stereotypes, underscoring the urgency of educational practices that challenge discriminatory norms. The study concludes that understanding how gender and race identities are socially constructed in childhood is essential for fostering more inclusive and equitable educational environments, contributing to the fight against structural inequalities in Brazilian society. Thus, the importance of Psychology and Pedagogy is reaffirmed in promoting a critical education committed to dismantling prejudice from the earliest stages of life.
Childhood, gender, and race: social perspectives in identity construction
Keywords: Infância; Gênero; Raça; Psicologia sócio-histórica; Pedagogia; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM